Greening MSW management systems by saving footprint: The contribution of the waste transportation. (1st August 2018) - Peri, G.; Ferrante, P.; La Gennusa, M.; Pianello, C.; Rizzo, G.
Abstract: Municipal solid waste (MSW) management constitutes a highly challenging issue to cope with in order of moving towards more sustainable urban policies. Despite new Standards call for recycling and reusing materials contained in the urban waste, several municipalities still use landfilling as a waste disposal method. Other than the environmental pressure exerted by these plants, waste transportation from the collection points to the landfill needs a specific attention to correctly assess the whole burden of the waste management systems. In this paper, the Ecological Footprint (EF) indicator is applied to the actual MSW of the city of Palermo (Sicily). Results show that the effects produced by the involved transportation vehicles are not negligible, compared to those generated by the other segments of the waste management system. This issue is further deepened by analysing the role of transportation in an upgraded waste management system that is represented by the newly designed waste management plan of Palermo. The computed saved ecological footprint is used here for suitably comparing the environmental performances of the MSW system in both scenarios. Finally, the suitability of the EF method to address not only complete waste management plans but also single segments of the waste management system, is also discussed. Highlights: Municipal Solid Waste Management plays a significant role in the EU circular economy. Transportation of waste is quite a relevant segment of the entire management system. The MSW management system of a city in the South of Italy is considered. The holistic approach provided by the Ecological Footprint method is used. Saved footprint is used to compare the performance of the MSW system in two scenarios.